Phage Display-Derived Monoclonal Antibodies Against Internalins A and B Allow Specific Detection of Listeria monocytogenes - Moreira, Gustavo Marçal Schmidt Garcia; Gronow, Sabine; Dübel, Stefan; Mendonça, Marcelo; Moreira, Ângela Nunes; Conceição, Fabricio Rochedo; Hust, Michael (Frontiers in Public Health, 2022)
Listeria monocytogenes is the causative agent of listeriosis, a highly lethal disease initiated after the ingestion of Listeria-contaminated food. This species comprises different serovars, from which 4b, 1/2a, and 1/2b cause most of the infections. Among the different proteins involved in pathogenesis, the internalins A (InlA) and B (InlB) are the best characterized, since they play a major role in the enterocyte entry of Listeria cells during early infection. Due to their covalent attachment to the cell wall and location on the bacterial surface, along with their exclusive presence in the pathogenic L. monocytogenes, these proteins are also used as detection targets for this species. Even though huge advancements were achieved in the enrichment steps for subsequent Listeria detection, few studies have focused on the improvement of the antibodies for immunodetection. In the present study, recombinant InlA and InlB produced in Escherichia coli were used as targets to generate antibodies via phage display using the human naïve antibody libraries HAL9 and HAL10. A set of five recombinant antibodies (four against InlA, and one against InlB) were produced in scFv-Fc format and tested in indirect ELISA against a panel of 19 Listeria strains (17 species; including the three main serovars of L. monocytogenes) and 16 non-Listeria species. All five antibodies were able to recognize L. monocytogenes with 100 % sensitivity (CI 29.24-100.0) and specificity (CI 88.78-100.0) in all three analyzed antibody concentrations. These findings show that phage display-derived antibodies can improve the biological tools to develop better immunodiagnostics for L. monocytogenes.